conversation in Pite Saami - Elsy Margareta Rankvist; Dagny Hildegard Skaile; Ann-Charlotte Sjaggo; Joshua Karl Wilbur; Michael Rießler (Joshua Wilbur, 2012)
Linguistic documentation of the Pite Saami language (ISO693-3: sje) Conversation about the old days, topics such as reindeer calves, coffee cheese, eating bear meat, seeing a bear, etc.